Mapping of urban above-ground biomass with high resolution remote sensing data - M. Aziz, NurAznim; Hashim, Mazlan (2007)

(untitled)
This paper reports on study carried out to determine and map the distributions and density of the urban total above-ground biomass (TAGB) content using high resolution satellite data of the SPOT-4 and Quickbird, with respective 10 and 4 meter spatial resolution for mapping two levels of urban biomass, Level I biomass derived at selected residential areas in Johor Bahru city urban landscape, and Level II biomass derived from SPOT-4 data in for the entire urban district (including the suburbs). The results of this study indicated that, Level I and Level II of biomass were derived at respective accuracy of Â±0.3kgm-2 and Â±0.4kgm-2, validated with in-situ verification.